PENGARUH SISTEM PENGENDALIAN INTERNAL, MORALITAS APARAT, DAN IMPLEMENTASI CORPORATE GOVERNANCE TERHADAP PENCEGAHAN KECURANGAN - Hielnanda Yasmin Azzahra; Reni Yendrawati (Jurnal Aplikasi Bisnis, 2022)
This study aimed to analyze the effect of internal control system, officer morality, and the implementation of corporate governance on fraud prevention. The sampling technique using purposive sampling technique. Sources of data used in this study is primary data, data obtained directly from respondents using a questionnaire. The sample in this study amounted to 50 respondents. This research using quantitative methods with multiple linear regression analysis and hypothesis testing use t test. The results of this study indicate that the internal control system have a positive effect on fraud prevention. Meanwhile, officer morality and corporate governance has no effect on fraud prevention.